Dissolved neodymium and hafnium isotopes and rare earth elements in the Congo River Plume: Tracing and quantifying continental inputs into the southeast Atlantic. (1st February 2021) - Rahlf, Peer; Laukert, Georgi; Hathorne, Ed C.; Vieira, Lúcia H.; Frank, Martin
Highlights: First dissolved Nd/Hf isotope and REE data from the Congo River Plume. High REE and Hf fluxes from the Congo River to the southeast Atlantic. Conservative river and surface seawater mixing of Nd/Hf isotopes and REEs/Hf at S > 23. Congo River particles impact intermediate and deep water signals of NE Angola Basin. Abstract: The Congo River is the second largest river by discharge in the world and a major source of element inputs into the South Atlantic Ocean. Yet, the element fluxes and transport mechanisms across and beyond its estuary and their impacts on the marine distribution and cycling of many major and trace elements are not well understood. We present the first combined dissolved neodymium (Nd) and hafnium (Hf) isotope and rare earth element (REE) concentration distributions following the Congo River plume along its flow path off the West African coast and along a connected offshore latitudinal section at 3°S. The Congo River freshwater itself is characterized by extraordinarily high Nd and Hf concentrations of up to 4000 pmol/kg and 54 pmol/kg, and by Nd (εNd ) and Hf (εHf ) isotope compositions that range between −15.6 and −16.4 and between 0.35 and −1.4, respectively. Our near- and offshore data indicate that at salinities above 23 conservative mixing of Congo-derived Nd and Hf concentrations and isotopic signatures with ambient surface seawater occurs for at least 1000 km to the northwest of the river mouth. This demonstrates a large spatial extent of the influence of the Congo plume on trace metal distributions in the eastern south Atlantic surface waters. A comparison between dissolved Nd and Hf fluxes from the Congo River and the shelf zone estimated based on radium isotope compositions indicate that release from Congo-derived particulate phases likely balances strong estuarine REE and Hf removal in the low salinity zone. The combined riverine and shelf zone flux for Nd is almost twice as high as that estimated for the Amazon River, despite that the Amazon discharge is about five times higher than that of the Congo River. Even the offshore Nd flux estimated for the 3 °S transect based on radium isotope compositions still corresponds to ∼40% of the Congo-shelf-zone flux and reaches 150 ± 50 Mg/year for Nd. Moreover, intermediate waters below the plume are strongly affected by exchange with particulate inputs from the Congo River given that Nd isotope signatures are inconsistent with values expected from large-scale water mass mixing and instead support unradiogenic Nd release either from sinking or deposited Congo-derived detrital material. Deep and bottom water isotopic signatures are also slightly affected by interaction with particles and benthic Nd release.